Development of Recombinase Aided Amplification Combined With Disposable Nucleic Acid Test Strip for Rapid Detection of Porcine Circovirus Type 2 - Chen, Wenxian; Fan, Jindai; Li, Zhaoyao; Zhang, Yuanyuan; Qin, Yuwei; Wu, Keke; Li, Xiaowen; Li, Yuwan; Fan, Shuangqi; Zhao, Mingqiu (Frontiers in Veterinary Science, 2021)
Porcine circovirus type 2 (PCV2) is the dominant causative agent of PCV2 systemic disease (PCV2-SD) in pigs. It can also associate with other diseases such as respiratory and enteric diseases, reproductive failure, porcine dermatitis, and nephropathy syndrome in pigs. Currently, PCV2 infection is a considerable threat in the swine industry. Therefore, it is of great significance to prevent, control, and accurately detect PCV2 in pig farms. Recombinase aided amplification (RAA) technology is an isothermal nucleic acid amplification technology that could rapidly amplify the target gene fragment at a constant temperature. The amplification products labeled with specific molecules could be visually detected using the test strip with the corresponding antibody. In the present study, the RAA technology combined with a nucleic acid test strip (RAA-strip) was established for simple and specific detection of PCV2. Primers and probes targeting the PCV2 ORF2 gene were designed according to the RAA technology principles. The PCV2 RAA-strip established in this study could detect as low as 103 copies/μL of recombinant plasmids containing the PCV2 ORF2 gene fragment. The lowest detection limit about viral DNA and virus titers was 6.7×10-6 ng/μL and 10 TCID50/mL, respectively. Furthermore, no cross-reaction with other porcine viruses occurred at 37 °C and within 15 min. We used 42 clinical samples to assess the performance of our established method. The positive rate of clinical samples detected by PCV2 RAA-strip was 50.00%. This was similar to that detected by PCV2 PCR (45.24%). In conclusion, due to the advantages of strong specificity, high sensitivity, excellent reproducibility, and simple operation method, our PCV2 RAA-strip is suitable for the rapid clinical detection of PCV2 on-site.